Anaerobic digestion of palm oil mill effluent (POME) in upflow biofilter reactors - Idris, Azni; Jusoh, Ahmad; Suki, Anhar; Megat Mohd Noor, Megat Johari; Ghazali, Abdul Halim (1990)
Anaerobic digestion is widely accepted as an effective method of treatment for high strength waste. In Malaysia,the agricultural industry is one of the major producer of high strength waste of which oil palm and rubber are the two main contributors. Serious pollution problems can be created if the waste goes untreated or uncontrolled. Most of the problems have been solved by the implementation of the conventional anaerobic tank and pond stabilization. The use of anaerobic filter for the treatment of Palm Oil Mill Effluent (POME),which essentially contains a very high suspended solids concentration,requires careful design because it is prone to the problem of clogging. In anaerobic biofilter,the presence of filter media anables bacterial mass to develop on the surfaces of the media as well as within the porous surfaces. The process retention time can thus be reduced since the cell residence time is enhanced,and also the immobilization of the biomass on the media prevents washouts unlike in the conventional system with a very short residence time. The study undertaken involved vertical upflow rectangular reactors to treat the POME. The initial stage of the study involved a reactor size of 30L with PVC filter media randomly packed. The reactor was later developed into a hybrid reactor (50L) by introducing a sedimentation compartment. The 50L reactor produced a destruction of 60% and 90% for COD and SS respectively. The introduction of a sedimentation cell into a larger biofilter system (277L) was successfull in removing 96% of the influent SS. This combination,also known as a hybrid reactor,was able to treat the high strength POME with a % COD removal of 93%.